Healthy Dietary Patterns Associated with Health Risk - Zayed, Aya Tariq; Saeed, Asst. Prof. Dr. Sami Khader (American Journal of Biology and Natural Sciences, 2026)
This study aimed to investigate the impact of dietary patterns on metabolic syndrome among students and staff at Tikrit University. Metabolic syndrome is associated with health risk factors such as obesity, hypertension, dyslipidemia, and hyperglycemia, which in turn increase the likelihood of developing heart disease and type 2 diabetes. The study employed an observational cross-sectional design and was conducted from September 24, 2024, to February 1, 2025. Data were collected using an online questionnaire that included sociodemographic information, an Intended Physical Activity Questionnaire (IPAQ), and an assessment of dietary intake using the Food Frequency Questionnaire (FFQ). A total of 667 participants had their body mass index (BMI) measured, and 223 completed the questionnaire. The results showed that the majority of participants were in the 18–32 age group, with a higher proportion of males than females. Furthermore, 66% of participants engaged in physical activity, and there was a higher proportion of structural and visceral fat in males compared to females. The study revealed that most dietary patterns showed no significant differences between the various groups, with the exception of differences observed in the consumption of potatoes, rice, and pasta, as well as sweets and snacks. The study concluded that the participants’ overall metabolic status was relatively good, but highlighted the need to promote nutritional awareness and physical activity within the university environment to reduce weight gain and the risk of future metabolic disorders.